(untitled) (Research, Society and Development, 2025)
Ionizing radiation represents a critical challenge in terrestrial contexts and, especially, in space exploration, where high levels of cosmic radiation threaten the safety of manned missions outside the Earth’s magnetosphere. In this scenario, radiotrophic melanized fungi emerge as a promising biotechnological alternative due to the unique ability of fungal melanin to absorb, dissipate, and attenuate ionizing radiation, as well as potentially converting some of this energy into metabolic benefits. This work aims to critically examine, through a literature review, the role of melanized fungi in the attenuation of ionizing radiation and evaluate their viability as an emerging biotechnological alternative for radiological shielding systems. This research, conducted through an exploratory and qualitative literature review, analyzed laboratory studies and experiments carried out on the International Space Station, which demonstrate increased growth and protective capacity of species such as Cladosporium sphaerospermum. The results indicate that fungal melanin can act as an efficient natural radioprotector, with applications aimed at building self-regenerating structures and shielding systems produced in situ in extraterrestrial environments. Although promising, advances are still limited by methodological gaps and the need for greater standardization and experimental depth. Thus, the potential of melanized fungi for the development of sustainable radiological protection technologies in both terrestrial and space environments is highlighted.